2023
DOI: 10.1155/2023/1227110
|View full text |Cite
|
Sign up to set email alerts
|

Based on the Results of PEDV Phylogenetic Analysis of the Most Recent Isolates in China, the Occurrence of Further Mutations in the Antigenic Site S1° and COE of the S Protein Which Is the Target Protein of the Vaccine

Abstract: The continuous challenge of existing vaccine systems by porcine epidemic diarrhea virus (PEDV) variant strains in recent years, it caused significant economic losses in the global swine industry. A PEDV virulent strain CH/HLJBQL/2022 was successfully isolated in China in this study. A genome-wide based phylogenetic analysis suggests that CH/HLJBQL/2022 belongs to the GII subtype, and 96.3%–99.6% homology existed in the whole genomes of other strains. For the first time, simultaneous mutations of four amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…One-hundred-eight (108) spike (S) proteins were extracted from the proteomes of PEDV GIIa strains retrieved from Yao, Qiao, et al . (2023) , Yao, Zhu, et al . (2023) , and Liu et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One-hundred-eight (108) spike (S) proteins were extracted from the proteomes of PEDV GIIa strains retrieved from Yao, Qiao, et al . (2023) , Yao, Zhu, et al . (2023) , and Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…One hundred eight PEDV GIIa strains used in the study were referenced from the phylogenetic trees constructed by Yao, Qiao, et al . (2023) , Yao, Zhu, et al . (2023) , and Liu et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a majority of coronavirus subunit vaccines in development target the RBD. Moreover, the NTD of S proteins from diverse animal coronaviruses have demonstrated carbohydrate receptor-binding activity, as observed in TGEV and IBV [ 208 , 209 ]. Recent studies have also indicated further mutations in the antigenic site S1° and COE of the PEDV S protein, making it a main candidate target for animal vaccine development [ 209 ].…”
Section: Main Targets For Animal Coronavirus Vaccine Developmentmentioning
confidence: 99%